Survival enhancing indications for coronary artery bypass graft surgery in California - Denton Timothy A; Rocke David M; Romano Patrick S; Marcin James P; Kravitz Richard L; Li Zhongmin; Brindis Ralph G; Dai Jian; Amsterdam Ezra A (BMC, 2008)
Abstract Background Coronary artery bypass graft (CABG) surgery is performed because of anticipated survival benefit, improvement in quality of life, or both. We performed this study to explore variations in clinical indications for CABG surgery among California hospitals and surgeons. Methods Using California CABG Outcomes Reporting Program data, we classified all isolated CABG cases in 2003-2004 as having "probable survival enhancing indications (SEIs)", "possible SEIs" or "non-SEIs." Patient and hospital characteristics associated with SEIs were examined. Results While 82.9% of CABG were performed for probable SEIs, the range extended from 68% to 96% among hospitals and 51% to 100% among surgeons. SEI rates were higher among patients aged ≥ 65 compared with those aged 18-64 (Adjusted Odds Ratio [AOR] > 1.29 for age groups 65-69, 70-74 and ≥ 75; all p < 0.001), among Asians and Native Americans compared with Caucasians (AOR 1.22 and 1.15, p < 0.001); and among patients with hypertension, peripheral vascular disease, diabetes, cerebrovascular disease and congestive heart failure compared to patients without these conditions (AOR > 1.09, all p < 0.001). Variations in indications for surgery were more strongly related to patient mix than to surgeon or hospital effects (intraclass correlation [ICC] = 0.04 for hospital; ICC = 0.01 for surgeon). Conclusion California hospitals and surgeons vary in their distribution of indications for CABG surgery. Further research is required to identify the roles of market factors, referral patterns, patient preferences, and local clinical culture in producing the observed variations.